2016
DOI: 10.1111/1753-0407.12410
|View full text |Cite
|
Sign up to set email alerts
|

Clinical inertia causing new or progression of diabetic retinopathy in type 2 diabetes: A retrospective cohort study

Abstract: Clinical inertia can cause persistently poor glycemic control and speed up the progression of DR in T2D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 17 publications
3
46
1
2
Order By: Relevance
“…Out of 7698 combined search results, 53 articles were identified that reported at least 1 measure of therapeutic inertia in the management of hyperglycaemia in individuals with type 2 diabetes . The main reasons for exclusion of publications other than duplicates and those covering irrelevant topics were that they reported non‐original research (eg, editorials, letters, comments and guidelines) or they were congress abstracts (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Out of 7698 combined search results, 53 articles were identified that reported at least 1 measure of therapeutic inertia in the management of hyperglycaemia in individuals with type 2 diabetes . The main reasons for exclusion of publications other than duplicates and those covering irrelevant topics were that they reported non‐original research (eg, editorials, letters, comments and guidelines) or they were congress abstracts (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies were conducted in North America (29 studies) and Europe (20 studies). Three studies were carried out in Asia, and a single study was conducted in Israel . Articles mainly reported data from cohort studies, using data from medical records or chart reviews, or from claims, clinical research or administrative databases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a UK study of patients treated with basal insulin who were clinically eligible for treatment intensification, only 31% had their treatment intensified, with a median time to intensification of 3.7 years . Delay in treatment intensification in patients with uncontrolled T2D has been shown to have a number of clinical consequences, including a significantly increased risk of myocardial infarction, heart failure, stroke, and a composite endpoint of cardiovascular events, as well as a higher incidence of (and significantly shorter median time to) progression of diabetic retinopathy . This progression of diabetes‐related complications with lack of treatment intensification in the overall T2D population is also seen in older adults …”
Section: Introductionmentioning
confidence: 99%